Keabsahan Akta Notaris Melalui Tindakan Hostile Takeover Pada Perseroan Terbatas Terbuka - Regina Adella Palmata Putri; Nefi, Arman (JUSTISI, 2024)
This research aims to ascertain and analyze hostile takeover actions occurring in Listed Companies, as well as the validity of notarial deeds resulting from hostile takeover activities. The research method employed by the author is normative or doctrinal legal research, utilizing a legislative approach along with a conceptual approach. The research findings are as follows: (1) There are various methods employed by aggressors in conducting a Hostile Takeover when the target company is a Listed Companies, namely through Tender Offer, involving the presentation of a cash offer to shareholders, and the acquisition of shares by the aggressor at an elevated price, aligning with the tender price rather than the market price. Another method is Proxy Fight, entailing persuasive actions to replace members of the board of directors to facilitate the takeover plan. (2) Regarding the validity of Notarial Deeds executed as a consequence of Hostile Takeover activities, they remain legally binding as long as their validity can be substantiated externally, formally, and materially. However, such deeds can be annulled through legal proceedings, provided there is a party seeking the annulment, and valid grounds for such action exist. Keyword : Notarial Dees; Hostile Takeover; Listed Company.